Genes in loci genetically associated with polycystic ovary syndrome are dynamically expressed in human fetal gonadal, metabolic and brain tissues - Azumah, Rafiatu; Hummitzsch, Katja; Anderson, Richard A.; Rodgers, Raymond J. (Frontiers in Endocrinology, 2023)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous disorder, affecting around 10% of women of reproductive age, with infertility, depression or anxiety, obesity, insulin resistance and type 2 diabetes as risk factors. The cause of PCOS is not known but there is a predisposition to developing PCOS in adult life that arises during fetal or peri-natal life. PCOS also has a genetic predisposition and a number of genetic loci associated with PCOS have been identified. These loci contain 25 candidate genes which are currently being studied to define the syndrome. Although the name PCOS suggests a syndrome of the ovary, PCOS has also been associated with the central nervous system and other organ systems in the body due to the wide variety of symptoms it presents. Methods: Here, we examined the expression patterns of PCOS candidate genes in gonadal (ovary and testis), metabolic (heart, liver and kidney) and brain (brain and cerebellum) tissues during the first half of human fetal development and post-natally until adulthood using public RNA sequencing data. Results: We found that the genes were dynamically expressed in the fetal tissues studied. Some genes were significantly expressed in gonadal tissues, whilst others were expressed in the metabolic or brain tissues at different time points pre-natally and/or post-natally. HMGA2, FBN3 and TOX3 were highly expressed during the early stages of fetal development in all tissues but least during adulthood. Interestingly, the correlation between expression of HMGA2/YAP1 and RAD50/YAP1 were significant in at least 5 of the 7 fetal tissues studied. Notably, DENND1A, THADA, MAPRE1, RAB5B, ARL14EP, KRR1, NEIL2 and RAD50 were dynamically expressed in all postnatal tissues studied. Conclusions: These findings suggest that these genes have tissue- or development-specific roles in multiple organs, possibly resulting in the various symptoms associated with PCOS. Thus the fetal origin of a predisposition to PCOS in adulthood could arise via the effects of PCOS candidate genes in the development of multiple organs.